Giant hornet (Vespa soror) attacks trigger frenetic antipredator signalling in honeybee (Apis cerana) colonies - Heather R. Mattila (The Royal Society, 2021)
Asian honeybees use an impressive array of strategies to protect nests from hornet attacks, although little is understood about how antipredator signals coordinate defences. We compared vibroacoustic signalling and defensive responses of Apis cerana colonies that were attacked by either the group-hunting giant hornet Vespa soror or the smaller, solitary-hunting hornet Vespa velutina. Apis cerana colonies produced hisses, brief stop signals and longer pipes under hornet-free conditions. However, hornet-attack stimuli—and V. soror workers in particular—triggered dramatic increases in signalling rates within colonies. Soundscapes were cacophonous when V. soror predators were directly outside of nests, in part because of frenetic production of antipredator pipes, a previously undescribed signal. Antipredator pipes share acoustic traits with alarm shrieks, fear screams and panic calls of primates, birds and meerkats. Workers making antipredator pipes exposed their Nasonov gland, suggesting the potential for multimodal alarm signalling that warns nestmates about the presence of dangerous hornets and assembles workers for defence. Concurrent observations of nest entrances showed an increase in worker activities that support effective defences against giant hornets. Apis cerana workers flexibly employ a diverse alarm repertoire in response to attack attributes, mirroring features of sophisticated alarm calling in socially complex vertebrates.